PENGARUH PENDEKATAN PEMBELAJARAN INDUKTIF TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS X SMA PAB 9 PATUMBAK - Riska Purnama Sari Tarigan; Nurjannah Nurjannah (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine the effect of the Inductive Learning Approach on Economic Learning Outcomes of Class X Students of SMA PAB 9 Patumbak. This research is associative, namely research that aims to determine the effect of two or more variables. This research uses a field study approach, namely a study based on facts that occur in the object of research. The population in this study were 28 students of Class X SMA PAB 9 Patumbak. The research sample that will be used in this research is the students of Class X SMA PAB 9 Patumbak totaling 28 students. The analysis technique used is simple regression analysis and hypothesis testing. The suitability test using simple linear regression and hypothesis testing (t test) was carried out to determine the effect of the Inductive Learning Approach on Economic Learning Outcomes of Class X SMA PAB 9 Patumbak. Based on the hypothesis test, it is known that there is a positive influence between the Inductive Learning Approach on the Learning Outcomes of Class X Economics at SMA PAB 9 Patumbak, this is evidenced by the tcount value of the Inductive Learning Approach variable of 3.688. This means that the value of tcount is greater than ttable (3,688 < 1,705) which indicates that the Inductive Learning Approach has a positive effect on student learning outcomes.